Destructive reconstruction in China: interpreting authenticity in the Shuidong Reconstruction Project, Huizhou, Guangdong Province - Zilin Yang (Built Heritage, 2021)
Abstract In the name of conservation, many local governments in China have demolished and reconstructed their historic districts using pseudo-antique architecture as part of their commercial developments. While the destructive reconstruction practice involves issues such as who plays the decisive role in defining authenticity in the targeted district considering the creativity and imagination entailed in reconstruction, few studies analyse the factors leading to changes in the interpretation of authenticity throughout the destructive reconstruction process. Through a discourse analysis on project portfolios and semi-structured interviews with government officials, project planners and Shuidong residents, this study investigates the interpretation and implementation of the national-level authenticity principles in the Shuidong Reconstruction Project in Huizhou, Guangdong Province. Narratives of authenticity in local heritage practices are constantly changing because of the shifting local politics and regulatory powers involved. The effectiveness of national-level authenticity principles at the local level relies largely on the establishment of sub-national heritage regulations and the authorisation of heritage, which draws inspections from upper-level administrations. This study reveals certain socio-political factors that affect the relationship between reconstruction practices and the interpretation of authenticity. The political and profit-oriented tendency of local heritage conservation practices in China demonstrates the mismatch between conservation ideologies and bureaucratic realities.